Konsep Bimbingan dan Konseling Perkembangan - Gioanny Pudji Pradana; Dio Achmad Fahreza; Aulia Syifa Febriansyah; Abdullah Bahtiar Giovanny; Aradhana Maheswara; Muhammad Aqmal Ahsanul Haq (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Developmental Guidance and Counseling (BK) is an approach that is oriented towards the development of individual potential optimally according to their developmental stage. Developmental BK emphasizes preventive and developmental aspects rather than just problem solving. This study aims to analyze the concept of developmental BK, its role in the world of education, and its implementation strategies. The research method applied is to conduct a literature review, which includes an analysis of various references from previous studies that are related to developmental BK. The study revealed that this approach is very effective in supporting students in understanding and completing their developmental tasks, improving their social-emotional abilities, and improving their academic achievement. Effective implementation of developmental BK requires careful planning, support from various parties, and the use of technology as a supporting medium. This article identifies various aspects such as (1) The concept of developmental BK (2) The philosophical basis of comprehensive BK (3) The components of basic service developmental BK, individual planning, and developing responsive services (4) System support (5) The philosophical basis of developmental BK in the form of written reports.